Wildfowl conservation in North America since 1945 - Bellrose, Frank C; Scott, Thomas G (Wildfowl, 1956)
During the decade following World War II, the pressures growing out of an increasing human population have added progressively to the difficulty of and need for waterfowl conservation. Moreover, the events taking place during these ten years have contributed little to suggest that the waterfowl conservationist's road will be any less difficult in the future. Waterfowl conservation during this period may be reviewed from three points of view: (1) administration, (2) management, and (3) research. As herein considered, administration embraces the political philosophy and financing of waterfowl management; management includes manipulation of waterfowl populations and habitat; and research concerns the gathering of facts upon which to base the management programme.